Manajemen Sarana dan Prasarana di Sekolah - Febriansyah, Riki; Handayani, Resi Widya (UNIVERSITAS SERAMBI MEKKAH, 2025)
ABSTRACT Management comes from the word to mange which means to manage. Management is carried out through a process and is managed based on the sequence and functions of management itself. Educational facilities and infrastructure are one of the important and main resources in supporting the learning process in schools, for that it is necessary to improve their utilization and management, so that the expected goals can be achieved. Educational facilities are one of the determining factors for the success of education. The completeness and availability of educational facilities in schools greatly affect the effectiveness and smoothness of learning in the classroom. Facilities are tools or objects that move to support effective and efficient learning activities in order to achieve educational goals, for example, notebooks, bulletin boards, student worksheets, computers, teaching aids, sports equipment, and practical equipment. While infrastructure is a tool or object that cannot move to support effective and efficient learning activities in order to achieve educational goals, for example, classrooms, teachers' rooms, administration rooms, principal's rooms, health facilities, canteens, fields, libraries, prayer rooms/places of worship, warehouses, halls, laboratories. School equipment management can be defined as a process of cooperation in utilizing all educational equipment effectively and efficiently. In essence, the management of educational facilities and infrastructure in schools is a process of utilizing all facilities and infrastructure owned by the school. All school facilities or infrastructure must be managed properly so that the existence of these facilities and infrastructure can support the learning process and be used as needed, so that learning in the classroom can run smoothly and educational goals can be realized. Keywords: Management; Facilities; Infrastructure.